Nickname Traditions And Turkic Folklore (Journal of Namibian Studies : History Politics Culture, 2023)
The nickname is an ancient tradition of Turkic peoples. Given that any ritual based on the ancient mythological notions, there is a wide range of old concepts such as anemism, totemism and believing in magic of words under this ritual. The origin of Turkic folklore nicknames dates back to ancient mythological notions. The human consciousness estimated the world as a three-level (low, medium, high) space and accepted that a person should receive a new name at passing from one world to another. The ancient Turkic texts clearly conformed that. The Kazakhs saved such an old Turks perception of world said some 19th century Russian scholars about Kazakh folklore and ethnography. In Turkic peoples history there were many historical leaders with pseudonyms such as Bilge Kagan (Mogilyan), the Turkic Khaganate founder, Genghis Khan (Temuchin), the Mongol Empire founder, Alasha (Sultan Ahmet khan), the youngest khan of Moghulstan. Take a look to the famous names in the 19 century Kazakh everyday life and culture like Shokan (Muhammad-Kanapiya Chingizoglu), Abay (Ibrahim Kunanbayuly). The nicknames really were in the life of believing ancients, and later became folkloric and an artistic means of glorifying the hero. We can see that the future official or hero oftenhad youth names or pseudonyms in Turkic epics plot. Nicknames were an inseparable part and plot of epics. Bukash  batyr and  Bamsy-Bairak on the Korkyt Ata Book and epics, Zhelkildek on a Kazakh fairy tale lived unknown before their heroic deeds. Abylai khan, Zhalantos, Kabanbai and others got nicknamed only after heroic deeds according to Kazakh historical legends.According to Turkic written monuments and the content of plots in folklore heritage, we see that pseudonym can be official or heroic depending on heroes social origin. Under wisdom and genius of a khan or ruler in governing the country the official nickname often means "competent", "wise", "younger". For example, Mogilyan - Bilge kagan, Tuman khan - Kun khan, Temuchin - Genghis khan, Zhanibek khan - Az Zhanibek, Tauke khan - Az Tauke and others. Khans acquired nicknames for their wisdom and genius in governing. In some Kazakh heroic songs, for example, in Shora Batyr song, the primary character gets a name from Muslim saints before the borning. Such a development repetes the scene of Oguz Kagan naming. So, hero nickname is a means for embellishment, glorification and idealization depending on changes in biography, ingenuity or other actions of hero.